2022
DOI: 10.3390/antiox11112270
|View full text |Cite
|
Sign up to set email alerts
|

On the Potential Role of the Antioxidant Couple Vitamin E/Selenium Taken by the Oral Route in Skin and Hair Health

Abstract: The relationship between oxidative stress and skin aging/disorders is well established. Many topical and oral antioxidants (vitamins C and E, carotenoids, polyphenols) have been proposed to protect the skin against the deleterious effect induced by increased reactive oxygen species production, particularly in the context of sun exposure. In this review, we focused on the combination of vitamin E and selenium taken in supplements since both molecules act in synergy either by non-enzymatic and enzymatic pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 268 publications
(312 reference statements)
0
6
0
1
Order By: Relevance
“…Serum levels of vitamin E levels appeared to be lower in patients suffering from PSO (as well as other chronic inflammatory skin diseases) compared to healthy individuals [ 37 ]. Vitamin E acts as an antioxidant protecting cell membranes from reactive oxygen species [ 68 ]. Indeed, it is advisable to evaluate vitamin E status in PSO and to supplement it when needed [ 37 ].…”
Section: Emerging Associations and Mechanisms Linked With Psoriasis A...mentioning
confidence: 99%
“…Serum levels of vitamin E levels appeared to be lower in patients suffering from PSO (as well as other chronic inflammatory skin diseases) compared to healthy individuals [ 37 ]. Vitamin E acts as an antioxidant protecting cell membranes from reactive oxygen species [ 68 ]. Indeed, it is advisable to evaluate vitamin E status in PSO and to supplement it when needed [ 37 ].…”
Section: Emerging Associations and Mechanisms Linked With Psoriasis A...mentioning
confidence: 99%
“…Vitamin E acts directly as an antioxidant, while selenium serves as a cofactor for GPx enzymes. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E acts directly as an antioxidant, while selenium serves as a cofactor for GPx enzymes. 57,58 SOD, GPx, and CAT are enzymes that play a role in neutralizing reactive oxygen species (ROS) in the body. ROS are highly reactive molecules produced as byproducts of normal cellular metabolism, capable of damaging cells and tissues.…”
mentioning
confidence: 99%
“…Adrenal hormone imbalance can enhance ROS production, causing oxidative damage to cells and tissues. Vitamin E aids in the scavenging of these damaging chemicals, thereby lowering oxidative stress ( 109 ). It has been demonstrated that vitamin E affects the body’s hormone levels, especially those of the adrenal glands.…”
Section: Role Of Nutritional Antioxidants In Alleviating Adrenal Horm...mentioning
confidence: 99%